Jim Stoppani's Encyclopedia of Muscle & Strength - Stoppani, J. (Human Kinetics, 2015)
Product Description Finally, a research-based book that covers all facets of optimizing the development of muscle and strength. Jim Stoppani`s Encyclopedia of Muscle & Strength, Second Edition, is a comprehensive training guide and reference that provides